Tool geometry evaluation for carbon reinforced composite laminates - L. M. P. Durão (2009)
The use of composite laminates in complex structures has increased significantly. However, there are still some issues when considering their use, mainly related with machining, leading to some difficulties and lack of acceptance. In this work, a methodology to evaluate drill geometry and feed rate based on thrust force and delamination extension is presented.